2003
DOI: 10.1029/2002gl015833
|View full text |Cite
|
Sign up to set email alerts
|

Novel Fabry‐Perot interferometer measurements of F‐region ion temperature

Abstract: [1] Novel optical measurements of F-region ion temperatures have been made in conjunction with thermospheric neutral temperatures. A ground-based FabryPerot interferometer has been used to observe high-latitude Fregion ion temperatures using the O + ( 2 P) auroral emission at 732 nm, and upper-thermospheric neutral temperatures using the O( 1 D) airglow emission at 630 nm. Dual wavelength measurements were made during February 2001 and clearly show that the ion temperature is equal to or greater than the neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 18 publications
0
9
1
Order By: Relevance
“…As noted here, Moore (1949) has been superseded by more recent determinations. The large differences between the wavelength and term splitting values determined here, and other older and/or widely-utilized values, warrant reconsideration of conclusions reached employing those standards, such as regarding F-layer physical conditions (Smith et al 1982;Cierpka et al 2003) and nebular velocity structure (Baldwin et al 2000).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…As noted here, Moore (1949) has been superseded by more recent determinations. The large differences between the wavelength and term splitting values determined here, and other older and/or widely-utilized values, warrant reconsideration of conclusions reached employing those standards, such as regarding F-layer physical conditions (Smith et al 1982;Cierpka et al 2003) and nebular velocity structure (Baldwin et al 2000).…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, recent ab initio and astrophysically observed calculations of the splitting argue for a significantly larger separation (see Table 1). Indeed, the newer values of the separation are larger than the 0.8Å quoted from Smith et al (1982) and measured by Cierpka et al (2003) by the order of the typical 0.1-0.8 km s −1 ion-drift velocities targeted for measurement by both studies. A larger 7320 separation also calls into question both the Cierpka et al (2003) interpretation of their observed line profile as the actual 7320 pair, and the accuracy of their F-layer temperature determination, made from a line profile fit in which the separation itself was a free parameter.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Sharpee et al (2004) measured the wavelengths of the O + ( 2 P-2 D) doublet components at 732.0 and 733.0 nm from a combination of HIRES sky spectra and spectra of distant nebulae. The wavelengths of the components of the 732.0 nm doublet were found to differ from the NIST values by 0.012 and 0.013 nm, and the spacing between the doublet components was found to differ by 0.02 nm from the value of Moore (1949) of 0.08 nm, which is still used as a figure of merit in estimating the accuracy of fits to Fabry-Perot profiles of these lines (Cierpka et al, 2003).…”
Section: Investigating Atomic and Chemical Properties Of Weak Componementioning
confidence: 97%
“…Metastable O + is studied predominantly through emission from the 2 P o term (at 5.0 eV above ground) rather than from the 2 D o term (at 3.3 eV) via the O + ( 2 P o – 4 S o ) 247 nm doublet [ Stephan et al , 2003] and the O + ( 2 P o – 2 D o ) 720 and 730 nm doublets [ Cierpka et al , 2003]. O + ( 2 D o ) should be produced copiously because the peak electron excitation cross section on O( 3 P ), the assumed auroral excitation mechanism for both 2 D o and 2 P o , is twice as big for the 2 D o term as it is for the 2 P o term [ Strickland et al , 1999].…”
Section: Observationsmentioning
confidence: 99%